2019
DOI: 10.6007/ijarped/v8-i2/5601
|View full text |Cite
|
Sign up to set email alerts
|

The Development Of Preschools’ Higher Order Thinking Skills (HOTs) Teaching Model towards Improving the Quality of Teaching

Abstract: The purpose of this study is to develop a preschools' higher order thinking skills (HOTS) teaching model. Some important aspects are also studied namely, the level of preschool teacher's thinking, the preschool teacher's view of the role played by the authorities, the needs of preschool teachers in implementing HOTS and the daily teaching practice of preschool teachers. The mixed method approach is used in this study. The quantitative study was analyzed using the SPSS version 23 software while the qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…It is considered that children learn especially through interaction with parents, teachers, and classmates, with added value being achieved for language learning and the development of positive dispositions towards the environment [33,34]. This confirms the relationship identified in the present research between collaboration and cooperation habits, hard-work and effort to learn, environmental habits, and personal hygiene.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is considered that children learn especially through interaction with parents, teachers, and classmates, with added value being achieved for language learning and the development of positive dispositions towards the environment [33,34]. This confirms the relationship identified in the present research between collaboration and cooperation habits, hard-work and effort to learn, environmental habits, and personal hygiene.…”
Section: Discussionsupporting
confidence: 85%
“…In all of them, teachers play a crucial role in ensuring that students acquire such habits. Considering the importance of this educational stage for children's subsequent development [32,33], alongside the decisive role exercised by teachers over children's learning acquisition, it is imperative to better understand good teaching practices which incentivize curiosity and interest within students. It will also be useful to uncover how to get them to acquire hygiene and health habits, whilst also promoting personal and interpersonal skills in order to establish relationships with classmates and cooperative working.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, one of the challenges in mathematics learning is the application of problem-solving skills among the teachers to the children [14]. Teachers need to apply different elements of problem-solving skills (expertise, skills, and values) during the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Yun (2012), primary school Science teachers in a rural area in Sarawak applied less of higher order thinking skills due to time constraints and they solely taught according to the syllabus to prepare students for examination, namely UPSR for primary schools. Latest research from Nachiappan et al (2019) reported that, the implementationof HOTS at preschool level is still at a moderate level as there are still less skilled teachers in implementing HOTS during the teaching and learninf process. Nonetheless, this study will examine the application of higher order thinking skills among rural school teachers.…”
Section: Literature Reviewmentioning
confidence: 99%